2021
DOI: 10.1002/ijgo.13648
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of maternal antibiotic prophylaxis in low‐ and middle‐income countries: Comparison to WHO recommendations for prevention and treatment of maternal peripartum infection

Abstract: Background: Sepsis is a leading cause of maternal death. Antimicrobials save lives, but inappropriate overuse increases risk of antimicrobial resistance. Objective: A scoping review comparing peripartum prophylactic antimicrobial use in low-and middle-income countries (LMICs) with WHO recommendations for prevention and treatment of maternal peripartum infection. Search strategy: Medline, Embase, Global Health, LILACS and the WHO Library databases were searched. Selection criteria: Publications from LMICs since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Studies in developing countries have reported that the proportion of deliveries that received antibiotics could reach up to 90% [ 16 , 17 ]. In Indonesia, study on prophylactic antibiotic use during delivery is very limited [ 18 ]. This situation immediately raised concern among experts, as previous studies had suggested that antibiotic exposure during labor and delivery may increase the risk of various adverse events to both the mother and newborn, including antibiotic-resistant bacterial infection, maternal and infant microbiome alteration, long-term functional impairment in children, and maternal anaphylaxis reaction [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in developing countries have reported that the proportion of deliveries that received antibiotics could reach up to 90% [ 16 , 17 ]. In Indonesia, study on prophylactic antibiotic use during delivery is very limited [ 18 ]. This situation immediately raised concern among experts, as previous studies had suggested that antibiotic exposure during labor and delivery may increase the risk of various adverse events to both the mother and newborn, including antibiotic-resistant bacterial infection, maternal and infant microbiome alteration, long-term functional impairment in children, and maternal anaphylaxis reaction [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations are supported by strong evidence on the impact and prevention of inappropriate use [ 14 , 23 , 24 ]. However, due to disparities in healthcare facilities, the guidelines for prophylactic antibiotic use in labor and delivery and the extent to which practitioners adopt these guidelines vary across countries, especially between high-income and low- to middle-income countries [ 14 , 18 ]. Despite the evidence that antibiotic use and inappropriate antibiotic prescriptions tend to be higher in low-income countries than in high-income countries, the practices of prophylactic antibiotic administration during delivery in low- to middle-income countries are not well characterized [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34] Implementation of World Health Organization recommendations has been shown to vary widely between countries. 35,36 Whilst Australia and other developed countries may have standardized protocols, varying levels of adherence to these protocols have been reported. 37 Communicating the potential risks of pre-incision antibiotics to patients is challenging, given it is now considered the standard of care.…”
Section: Antib Iotic Prophyl a Xis For Ce Sare An S Ec Ti On: Current...mentioning
confidence: 99%
“…Overall, most of the studies on antibiotic prophylaxis have supported the current [2] recommendation on the use of antibiotics in the prevention of maternal peripartum infection. Implications for policy makers and practitioner's in health systems and for better public health outcomes is to recognize the importance of protocols on prophylaxis antibiotic use in maternity units based on the best available evidence, conformance to the standards of infection prevention and control as well as observance of surgical procedures [49]. In addition, policy makers and practitioners should consider systems approach in the prevention of maternal peripartum infections apart from antibiotic prophylaxis alone.…”
Section: Antibiotic Prophylaxismentioning
confidence: 99%